Curated and Asymmetric Exposure: A Case Study of Partisan Talk during COVID on Twitter - An, Zijian; Breuhaus, Jessica; Niu, Jason; Sariyuce, A. Erdem; Joseph, Kenneth (Proceedings of the International AAAI Conference on Web and Social Media, 2024)
Social media has been at the center of discussions about political polarization in the United States. However, scholars are actively debating both the scale of political polarization online, and how important online polarization is to the offline world. One question at the center of this debate is what interactions across parties look like online, and in particular 1) whether increasing the number of such interactions is likely to increase or reduce polarization, and 2) what technological affordances may make it more likely that these cross-party interactions benefit, rather than detract from, existing political challenges. The present work aims to provide insights into the latter; that is, we focus on providing a better understanding of how a set of 400,000 partisan users on a particular social media platform, Twitter, used the platform’s affordances to interact within and across parties in a large dataset of tweets about COVID in 2021. Our findings suggest that Republican use of cross-party interaction were both more potent and potentially more strategic during COVID, that cross-party interaction was driven heavily by a small set of users and conversations, and that there exist non-obvious indirect pathways to cross-party exposure when different modes of interaction are chained together (especially retweets of quotes). These findings have implications beyond Twitter, we believe, in understanding how affordances of platforms can help to shape partisan exposure and interaction.